STUDI PEMANFAATAN LIMBAH CO2 MENJADI CO2 CAIR DENGANTEKNOLOGI CO2 PURIFICATION DI INDUTRI BAJA - Kartika, Wahyu (Jurnal Jaring SainTek, 2021)
Steel products are needed to support thedevelopment of the manufacturing industry andother strategic industries in Indonesia. Thesteel industry is one of the contributors to CO2 gas emissions, which contributes about 15percent of greenhouse gases (GHG). PT. XYZ,which is one of the largest steel industries inIndonesia, produces CO2 waste from thereduction process in the exhaust gas by anaverage of 20 tons/hour to produce its steel.This study aims to utilize CO2 waste in exhaustgas into liquid CO2 so that its utilization canreduce CO2 emissions to the environment.Waste minimization by PT. XYZ is by recyclingCO2 waste into liquid CO2 with CO2 Purification technology. Liquid CO2 is usefulin various industries such as the manufactureof carbonated beverages, food and beveragepreservation, and the welding industry. Wasteminimization has resulted in a 10% reductionin CO2 emissions by an average of 10%. Themagnitude of this decrease is influenced by thelimited production capacity and storage tankcapacity. The results of the study also showthat the variables that are considered for theuse of CO2 emissions are the purity of CO2,raw gas CO2.